Fourth Five-Year Plan (1969-74) Madras State Draft Outline - Planning Commission (Planning Commission, 1968)
Economic Planning for any region has necessarily to begin with an analysis of the basic physio-geographic data relating to the region and an appraisal with reference to such data of the potential of natural resources, the present pattern of utilisation and prospects of future development. Madras State can be divided into four essential physio-geographic regions : (I) the Coastal Plain ; (ii) the Eastern Ghats ; (iii) the Central Plateau, and. (iv) the Western Ghats. The Coastal Plain stretches for 620 miles (998 kms.) from Pulicat lake to Cape Comorin.
Madras State